Attitude of Farmers towards Groundnut Cultivation in Bikaner District of Rajasthan (Indian Journal of Extension Education, 2021)
The National Mission on Oilseed and Oil Palm (NMOOP) in India aims to increase oil seed and oil palm production and productivity by converting fallow lands to oilseed crops and diversifying regions away from low-yielding cereals. It plans to improve vegetable oil availability and reduce edible oil imports by increasing oilseed production and productivity from 29.79 million tons and 1122 kg/ha in the 12th plan period to 36.10 million tons and 1290 kg/ha by the end of 2019-20. The study, aimed to explore respondents’ opinions towards groundnut cultivation was conducted on 80 beneficiary farmers of NMOOP and 80 non-beneficiaries. Groundnut growers, accounting for 11.24 percent, had a less favorable attitude toward groundnut cultivation whereas, 69.38 per cent of respondents fell into the moderately favorable category. It was noted that the both category of respondents had favorable attitude towards the interventions of groundnut cultivation.